Effort-reward imbalance and overcommitment at work in medicine and nursing faculty in a public institution (Revista Gestão & Saúde, 2015)
Occupational stress studies with effort-reward imbalance at work in medical and nursing faculty have not been described in literature. Objectives: 1) To estimate the effort-reward imbalance and the overcommitment at work in medical and nursing faculty. 2) To verify if there is an association of those variables according to faculty groups. Method: A cross-sectional study was achieved with 232 professors of a public institution in São Paulo State from April to November in 2009. Applied instruments: a sociodemographic and occupational questionnaire and an effort-reward imbalance at work questionnaire (Effort-Reward Imbalance ”“ ERI). The chi-square test was used to verify the association of variables between faculty groups. Results: Prevalence of effort-reward imbalance was 31.3% in nursing faculty, 14.1% in medical faculty and 17.7% in overall sample, with significant difference between faculty (p = 0.006). Prevalence of overcommitment at work was similar in nursing and medical faculty as well as in overall sample (45.8%, 39.7% and 40.9% respectively), without any significant difference between faculty (p = 0.738) . Conclusions: The effort-reward imbalance in nursing faculty was 2.2 times higher compared to medical faculty. Both faculty groups presented a high prevalence of overcommitment at work, which denotes remarkable personal characteristics of better controlling needs and difficulty in relaxing after work in those professions. Further studies may contribute to preventive and interventional measures related to occupational stress in medical and nursing faculty. Keywords: Burnout. Occupational stress. Epidemiology. Medical Faculty. Nursing Faculty.